Competitiveness seen through the prism of corporate organizational culture – a theoretical study - Leśniewski, Michał Adam (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The problem of competitiveness is a great challenge not only for the business practice of enterprises but also for management and quality sciences. Competitiveness is an inseparable element (factor) related to achieving and maintaining competitive advantage on the market. It can be perceived as the total of factors (e.g. all the resources of an organization) constituting an economic entity or as a selected factor (e.g. organizational culture), thanks to which the organization will achieve and maintain a competitive advantage. The aim of the study is to present in the theoretical sphere of competitiveness seen through the prism of organizational culture. The considerations presented in this study are based on an interpretative study of the literature on the subject. The combination of competitiveness and organizational culture is fully in line with the interests of soft management and soft competitiveness.